2016
DOI: 10.7127/rbai.v10n300390
|View full text |Cite
|
Sign up to set email alerts
|

Qualidade Da Água Drenada E Desenvolvimento Do Feijão-Caupi Em Solos Salino-Sódicos Após Uso De Gesso Associado À Lâmina De Lixiviação

Abstract: RESUMOA salinização e a sodificação dos solos representam dois dos principais problemas das áreas cultivadas na região semiárida do Nordeste brasileiro, responsáveis pela redução da produção agrícola. O objetivo deste trabalho foi avaliar a influência do uso de diferentes níveis de gesso associado à lâmina de lixiviação parcelada em dois solos salino-sódicos sobre a qualidade da água de drenagem e no desenvolvimento do feijão-caupi. Para o estudo foram utilizadas colunas de PVC, as quais foram preenchidas com … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…Mean values of grain size composition, soil density and particle size of a fluvic entisol affected by salts 15 2.5 Turbidity-uT 5 1.78 Electrical conductivity -µS/cm a 25º C *** 68 pH 6.0 to 9.5 These results indicate that the use of low-cost organic inputs available on farms can satisfactorily contribute to the recovery of soils affected by salts, but the combination with gypsum may result in an even higher infiltration rate [24,25]. The use of gypsum together with an organic matter source has shown good results both for crops and for the process of improving the physical-water conditions [26,27,28]. Previous studies have also indicated that the addition of crop residues to the soil can improve several aspects of a saline-sodic soil, such as water infiltration rate [29].…”
Section: Resultsmentioning
confidence: 99%
“…Mean values of grain size composition, soil density and particle size of a fluvic entisol affected by salts 15 2.5 Turbidity-uT 5 1.78 Electrical conductivity -µS/cm a 25º C *** 68 pH 6.0 to 9.5 These results indicate that the use of low-cost organic inputs available on farms can satisfactorily contribute to the recovery of soils affected by salts, but the combination with gypsum may result in an even higher infiltration rate [24,25]. The use of gypsum together with an organic matter source has shown good results both for crops and for the process of improving the physical-water conditions [26,27,28]. Previous studies have also indicated that the addition of crop residues to the soil can improve several aspects of a saline-sodic soil, such as water infiltration rate [29].…”
Section: Resultsmentioning
confidence: 99%